Fabrication and characterization of ZnO-Sn02 mixed nanostructures - Tharsika, Thabothanayakam; Haseeb, A.S. Md. Abdul; Mohd Faizul, M.S. (2013)
In recent years, ZnO, Sn02 nanostructures have received special attention of researchers due to their potential in commercial applications. ZnO and Sn02 mixed materials are promising materials for several applications such as gas sensing and optoelectronic devices 1. Many methods have been introduced for the fabrication of mixed metal oxide nanostructuresi". Most of them involve multiple processing steps which results a core-shell or hierarchical nanostructures. In this work, ZnO-Sn02 mixed nanostructures were sYnthesized by a single-step carbothermal reduction method by vapor liquid solid mechanism. The Morphology and crystal structure of fabricated mixed nanostructures were characterized by field emission scanning electron ~icroscope (FESEM), transmission electron microscope (TEM) and X-ray diffraction (XRD). XRD results Indicated that the ZnO-Sn02 mixed nanostructures possessed crystalline structure. FESEM images revealed the uniform nanowires with diameter ranges from 15 nm to 80 nm and length of several tens of micrometers. The distribution of elemental Zn and Sn were found in mixed form in the nanowire which was confirmed by elemental mapping of TEM images. These ZnO-Sn02 nanostructures can be employed in chemical sensing, photovoltaic and photocatalysis applications.